HUBUNGAN TERAPI OKSIGEN DENGAN INSIDEN RETINOPATHY OF PREMATURITY (ROP) PADA BAYI PREMATURE - Banin, Servasius Ratu; Saleh Nuwa, Muhammad (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
This literature review aims to explore the relationship between oxygen therapy and the incidence of ROP in premature infants. A literature review was performed for this research. Literature searches both internationally and nationally use Scopus, ScienceDirect, Google Scholar, and Pubmed databases. The keywords used in the search are "Oxygen Therapy" AND ROP. In the initial stage of the search, 170 journal articles were obtained. Of these, about 6 articles are considered relevant. Premature babies who received oxygen therapy had a 10.20 times greater risk of developing ROP compared to babies who did not receive oxygen therapy. Premature babies who receive oxygen therapy using nCPAP were shown increased risk of ROP. The duration of oxygen therapy also plays an important role in determining the occurrence of ROP. Premature infants who received oxygen therapy for 39.34 days and above experienced ROP. The administration of FiO2 and the oxygen saturation target that is too high also increases the risks of ROP. Premature babies who receive oxygen therapy have a greater risk of developing ROP than babies who do not receive oxygen therapy. Oxygenation with nCPAP, high oxygen saturation and concentration, and duration play an important role in causing ROP